Chemistry Study and Entrepreneurship Program for the younger generation at Sanggar Bimbingan Sentul, Kuala Lumpur Malaysia - Wijaya, Anugrah Ricky; Syah, Alif Alfarisyi; Putra, Helwani Fuadi Sujoko; Kusumaningrum, Irma Kartika; Pramesti, Indah Nur (Universitas Negeri Malang, 2023)
The issues faced by the sons and daughters of Indonesian citizens (WNI) in Malaysia are social inequality, access to education, and a sense of community involvement. Sanggar Bimbingan Sentul, as a partner, provides learning facilities for WNI's children to solve these three main problems. We initiated to apply the program of MAWIRAKI (Matahari Kewirausahan Kimia) with chemistry study and entrepreneurship program through the Pengabdian Kemitraan Luar Negeri (PKLN) grant by Universitas Negeri Malang (UM). This program integrated by computer training with MS-Word and Paint programs, chemistry daily-life experiments, and the art of batik craft. The results of learning process WNI's children shows that 18 favored students in the Paint program and 10 in the MS Word program during computer training. The